Towards the Implementation of the New Urban Agenda Contributions from Japan and Germany to Make Cities More Environmentally Sustainable (Springer International Publishing, 2018)
This book looks at the New Urban Agenda and prospects of its implementation. In 2016, the New Urban Agenda was endorsed by the General Assembly of the United Nations after having been adopted by the United Nations Conference on Housing and Sustainable Urban Development (Habitat III) in Quito, Ecuador. Together with the Sustainable Development Goals, it provides a comprehensive and ambitious roadmap for global debate and action related to sustainable urbanisation during the coming decades. As mature economies and ageing societies, Japan and Germany can make considerable contributions to the implementation of the New Urban Agenda. Both countries share a number of similar challenges for environmentally sustainable and resilient urban development under conditions of social change. Furthermore, they have vast experience in actively promoting urban transformation towards a more sustainable urban future. At the same time the authors are making a contribution towards implementing the New Urban Agenda. Other countries may build up on the experience provided and the 20 examples described in this book. The work is based on a longstanding cooperation between the Graduate School of Environmental Studies of the Nagoya University (Japan), the Leibniz Institute of Ecological Urban and Regional Development (Germany) and the Technische Universität Dresden (Germany).